2004
DOI: 10.1055/s-2004-821273
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Sternal Blood Flow after Different Methods of Internal Thoracic Artery Harvesting

Abstract: Skeletonized and semiskeletonized ITA harvesting techniques caused a similar acute reduction in sternal perfusion during the early postoperative period and this effect lasted for at least 5 hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Proponents of skeletonized BIMA harvest claim that the sternal blood supply is preserved with this technique, perhaps contributing to a lowering of the incidence of sternal wound complications in general and in diabetics in particular [Peterson 2003;De Paulis 2005;Nakano 2008]. This concept stems from animal studies, which have reported greater residual retrosternal blood flow after minimized retrosternal tissue mobilization with the skeletonization technique [Parish 1992;Fokin 2004], as well as from a small randomized study that used nuclear imaging [Boodhwani 2006]. This concept has recently been contradicted by Nishi and colleagues [2011].…”
Section: Discussionmentioning
confidence: 99%
“…Proponents of skeletonized BIMA harvest claim that the sternal blood supply is preserved with this technique, perhaps contributing to a lowering of the incidence of sternal wound complications in general and in diabetics in particular [Peterson 2003;De Paulis 2005;Nakano 2008]. This concept stems from animal studies, which have reported greater residual retrosternal blood flow after minimized retrosternal tissue mobilization with the skeletonization technique [Parish 1992;Fokin 2004], as well as from a small randomized study that used nuclear imaging [Boodhwani 2006]. This concept has recently been contradicted by Nishi and colleagues [2011].…”
Section: Discussionmentioning
confidence: 99%
“…This is relevant because incipient sternal dehiscence is often related to the distal part. 34 In contrast, the force distribution in the CSR was completely different. Because of the curved profile, the sternum touches the retractor first at the middle, and the highest forces in the middle section of the retractor blades result from that geometric fact.…”
Section: Discussionmentioning
confidence: 97%
“…Our vascular perfusion study has profoundly impacted our surgical planning and reinforced the necessity of incorporating bilateral IMAs for perfusion of the allograft. Although multiple studies report decreased postoperative ipsilateral sternal perfusion following the use of the left IMA for coronary revascularization, [31][32][33] infectious complications usually manifest after bilateral IMAs are utilized. 35 This has led to the perception that one IMA can perfuse the ipsilateral and contralateral chest wall.…”
Section: Discussionmentioning
confidence: 99%